GLOBAL MARKET OF SPACE PRODUCTS AND SERVICES: PROBLEMS AND PROSPECTS - S. Bondarev; S. Verigo (Вестник университета)
An analysis of consumer demand for products of the space industry has been presented. The main goals and objectives of the largest exporting countries, which present in the international markets of high-tech products manufacturers have been defined. The incentives for the development of space activities in individual countries and the possibility of commercialization in the system of promoting space products and services to international and domestic markets have been investigated. The current and forecast estimates of global exports as information products of global navigation satellite systems (GNSS) and remote sensing of the earth have been given.